2023
DOI: 10.3390/molecules28062870
|View full text |Cite
|
Sign up to set email alerts
|

Targeted HPTLC Profile, Quantification of Flavonoids and Phenolic Acids, and Antimicrobial Activity of Dodonaea angustifolia (L.f.) Leaves and Flowers

Abstract: In East Africa, Dodonaea angustifolia (L.f.) is a well-known medicinal herb. Its leaf is primarily studied in light of its ethnobotanical use. In terms of phytochemistry and biological activity, its flower is not studied. In a prior study, our team looked into phytochemical screening, antioxidant activity, and total phenolic levels. This study aims to compare the profiles and biological activities of the leaf and flower samples of D. angustifolia and to present therapeutic alternatives. The leaf and flower sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…Therefore, the current investigation addresses this research gap through the HPTLC profiling and quantification of the three fruits, the seed, and the peel. The phenolic contents of the studied wild edible fruits were comparable to the reported medicinal plants, as indicated by the previously reported values of 0.0801 to 0.2182 µg/100 mL [35]. result, the SST correlations (R 2 ) of most of the standards with the target compounds in the samples ranged from 0.57 to 0.999%.…”
Section: Optimization Of High-performance Thin-layer Chromatography-u...supporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, the current investigation addresses this research gap through the HPTLC profiling and quantification of the three fruits, the seed, and the peel. The phenolic contents of the studied wild edible fruits were comparable to the reported medicinal plants, as indicated by the previously reported values of 0.0801 to 0.2182 µg/100 mL [35]. result, the SST correlations (R 2 ) of most of the standards with the target compounds in the samples ranged from 0.57 to 0.999%.…”
Section: Optimization Of High-performance Thin-layer Chromatography-u...supporting
confidence: 86%
“…The fingerprints of the HPTLC chromatograms (overlay and stacked) obtained from the previously optimized UAE of the dried fruit powders showed that most of the targeted flavonoids and phenolic acids were identified in most of the fruit powders (Figure 2a-d). The obtained fingerprint of the HPTLC chromatogram (Figure 2a-d) of fruit extracts represents unique biologically active components [35]. The HPTLC-enhanced scans (photograph) of the developed plates (chromatograms) revealed the presence of gallic acid, chlorogenic acid, syringic acid, quercetin, myricetin, kaempferol, and rutin in many of the different dried fruits (Figure 2a-d).…”
Section: Optimization Of High-performance Thin-layer Chromatography-u...mentioning
confidence: 96%
See 2 more Smart Citations
“…Some reports have predicted that deaths due to antimicrobial-resistant bacteria will reach up to 10 million in the year 2050 [8]. Several synthesized substances have been used to fight microbes and bacteria (e.g., Shigella) [9,10].…”
Section: Introductionmentioning
confidence: 99%